Analisis Kemampuan Literasi Spasial Pada Materi Mengenal Peta Siswa Kelas IV SDN 060921 Medan - Demmina Ginting; Dian Armanto; Anita Yus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The problem in this research lies in the lack of students' spatial literacy skills in the material "knowing maps" especially in understanding symbols, distance, and determining location. Therefore, the purpose of this study is to describe in depth how students' spatial literacy skills in the material "knowing maps" in grade IV SDN 060921 Medan. This study uses a qualitative descriptive approach method, involving grade IV teachers and grade IV students. Data collection was carried out through interviews, observation, and documentation, and analyzed using the modelMiles and Huberman.The results of the study showed that the average spatial literacy ability in the map recognition material was 63.75, or had not yet reached the Learning Objective Completion Criteria (KKTP). This was because students found it difficult to read symbols, indicate directions, and determine the location of an area. Furthermore, teachers focused solely on map images in textbooks, so students felt they lacked understanding. The solution to this problem is to teach map material slowly, connect it to students' real lives, and create digital map media.. To realize this solution, the fourth-grade teacher sought resources to support the creation and use of the designed media. Furthermore, the teacher committed to teaching the material slowly and connecting it to the students' real lives.